L’Art de la manière et la pratique de la pointe dans les Sonnets de Shakespeare et le Premier Livre des Amours de Ronsard - Louis Picard (Etudes Epistémè)
In the system of the sonnet, the conceit is a crystallization. Within its small confines, it manages to conflate the logical outcome of the poem and a feat of formal brilliance. Art within art, it meets the demands of the respice finem principle by engaging the whole piece. This is where style is at its most visible, as the poetical manera is highly condensed. But the conceit also calls for a specific poetics. It is therefore an essential feature of Ronsard’s and Shakespeare’s collections of sonnets, for their mannerism, fuelled by the conscience of not coming first, of writing after Petrarch — perhaps even against Petrarch —, requires a poetics of prowess, shifting the weight from res to verba. In these poems, the conceit has a double function: structural and dynamic. It concludes the piece in a logical way and calls for an effects-oriented virtuosity. Its highly sophisticated intricacy is just as crucial as the meaning it carries, in such a way that they merge completely. With the conceit, the sonnet ends in a verbal cornucopia that will not be converted into any stable meaning. Be it, as with Ronsard’s Premier Livre des Amours, a highly meaningful spectacle calling for rapture or, as with Shakespeare’s Sonnets, a suggestion asking for the reader’s assent while suspending it, the conceit’s gnomic brilliance could be seen as the relative and astonishing shape truth assumes in the poetic order of things. Under the aegis of the jocus serius, its hyperbolic radiance is a frail reflection as well.